Helpers, employees or owners: Opportunities for women's empowerment in agricultural value chains - Moreno, Manuel; Twyman, Jennifer; Wiegel, Jennifer Rebecca; Muriel, Juliana; Chavarro, Mónica Juliana; Suazo, Carlos; Castro, Judith (Bioversity International and the International Center for Tropical Agriculture, 2021)
The main objective of this study is to explore women's empowerment in cashew and dairy value chains (of the Gulf of Fonseca in Honduras) in order to identify opportunities and barriers that women face to be involved as employees, owners, and/or managers in the production and processing nodes. What is the relative performance of different agricultural value chains in terms of women’s empowerment? What factors influence women's empowerment in the different value chains and the different nodes of these value chains? What opportunities and barriers exist for women in terms of economic opportunities (and/or assuming different roles such as employee, manager, or owner)? This work is undertaken as part of, and funded by, the CGIAR Research Program on Policies, Institutions, and Markets (PIM) led by the International Food Policy Research Institute (IFPRI), in collaboration with Swisscontact.